Minimally Invasive Coronary Bypass Grafting as a Standard Approach for Myocardial Revascularization - O. D. Babliak; V. M. Demianenko; D. Y. Babliak; A. I. Marchenko; E. A. Melnyk; O. S. Stohov (Ukrainian Journal of Cardiovascular Surgery, 2020)
Background. Minimally invasive cardiac surgery is becoming more widespread.The aim of the study was to evaluate the outcomes in 343 consecutive patients with isolated multivessel coronary artery disease who underwent minimally invasive coronary revascularization.Materials and methods. From July 2017 to December 2019 we performed total coronary revascularization via left anterior minithoracotomy (TCRAT) in 343 consecutive patients with isolated multivessel coronary artery disease. In 83 (24.2%) of them we performed multiarterial revascularization using left internal mammary artery (LIMA) and T-shunt with left radial artery or right internal mammary artery (RIMA). Cardiopulmonary bypass (CPB), aortic cross-clamping and blood cardioplegia were used in all patients. The patients were divided into two groups, uniarterial and multiarterial, to compare and analyze perioperative parameters.Results. No cases of postoperative myocardial infarction, surgically induced infection, or conversion to sternotomy were observed in any of the study groups. Total perioperative mortality was 0.58% (2 patients). Total operation time (290.6±48 [205; 495] versus 259.4±53.3 [165; 590], p=0.0001) and aortic cross-clamping time (81.6±18.7 [40; 122] versus 67±18 [35; 146], p<0.0001) were longer in patients with multiarterial revascularization compared to those with uniarterial revascularization. The patient’s mean age in the multiarterial group was 7.4 years less than in the uniarterial group. The mean hospital stay was 0.5 days shorter in the multiarterial group.Conclusions. The technique of minimally invasive coronary artery bypass grafting via left anterior thoracotomy avoids median sternotomy in 97.7% of patients. Both strategies for minimally invasive myocardial revascularization (multiarterial and uniarterial) are safe and effective with comparable perioperative outcomes and a total mortality of 0.58%.